Kapwa Agta an awareness campaign on the rights of indigenous peoples and ancestral domain empowering the Agtas of Casiguran in raising solidarity for collective action in addressing the displacement caused by the development of APECO (RA 10083) - Dela Concepcion, Ana Sofia V.
Ancestral domain is rich in vast lands, sprawling forests and abundant watersheds. Many of the Philippines' natural resources thrive in these territories. Indigenous cultural communities have settled and continue to maintain the flora and fauna of their respective ancestral domain throughout the country. Since the onset of the colonial period of the Philippines, indigenous peoples have been facing problems of displacement and ownership. These problems sprout into numerous forms of human rights and violations that have been carried on to the Indigenous Peoples of the Philippines today. Many investors and developers take interest on the Ancestral Domain because of its abundance in natural resources. This causes the nationwide struggle of protecting Indigenous People's culture.